Association between Motor Skills, Occupational Performance, and Mental Health in Japanese Children with Neurodevelopmental Disorders: A Cross-Sectional Correlational Study - Masanori Yasunaga; Hideki Miyaguchi; Chinami Ishizuki; Yosuke Kita; Akio Nakai (MDPI AG, 2024)
Background: Motor skills have been linked to executive functions (EFs) in children with developmental coordination disorder (DCD). However, the traits of other neurodevelopmental disorders (NDDs), such as attention-deficit/hyperactivity disorder and autism spectrum disorder, remain overlooked. Therefore, this study explored the association between motor skills, occupational performance, and mental health in older kindergarten children with DCD and other NDDs. Overall, 95 participants aged 5-6 years were included in this study and divided into four groups: DCD traits (DCD-t), DCD-t + NDD traits (DCD-t + NDD-t), NDD-t-only, and typically developing children. Motor skills, EFs, and mental health were assessed using the DCD Questionnaire (DCDQ-J) and Movement Assessment Battery for Children-Second Edition, School Assessment of Motor and Process Skills (S-AMPS), and the Strengths and Difficulties Questionnaire (SDQ), respectively. The DCD-t + NDD-t group exhibited a strong correlation between the S-AMPS motor skill score and the DCDQ-J fine motor skill score (r = 0.88, p < 0.001) and between the total DCDQ-J score and the SDQ Total Difficulties Score (r = −0.94, p < 0.001). The findings indicate that children with DCD-t and NDD-t are more likely to experience EF and mental health problems than those with DCD-t only.